Estimation of out-of-pocket expenditures on health in a coastal rural community in Karnataka, India - P. Monisha Mary; Ankeeta Menona Jacob; J. Jithin Daniel; Avinash K. Shetty (Social Sciences and Humanities Open)
Introduction: Out-of-pocket health expenditure (OOPE) imposes a significant financial burden on households, especially in low- and middle-income countries like India. OOPE increases economic inequality and poverty, as families are forced to bear high healthcare costs. Health insurance has emerged as a key strategy for reducing OOPE and advancing Universal Health Coverage (UHC). However, health insurance coverage in Karnataka remains below the national average, leaving many vulnerable to financial hardships. This study aimed to evaluate the extent of OOPE and assess the role of health insurance in reducing financial strain in a coastal rural community in Karnataka. Methods: A cross-sectional descriptive study was conducted between June and August 2023 in a rural community covered by the “Nere-kere-KSHEMA” health insurance scheme. A total of 222 households were surveyed using a structured questionnaire, which gathered data on socio-demographic characteristics, health insurance coverage, and medical expenses. Data were analyzed using Jamovi version 2.3.38 with descriptive and inferential statistics to identify significant associations between health insurance coverage and OOPE. Results: The study found that 144 (59.5 %) of households were covered by health insurance. Despite this, 84 (34.7 %) of insured households and 52 (21.5 %) of uninsured households experienced catastrophic OOPE. Hospitalisation rates were higher among insured households, yet many still faced substantial financial consequences, including taking loans, selling assets, and losing wages. Although insured households experienced a slightly lower financial burden compared to their uninsured counterparts, OOPE remained a considerable issue. Conclusion: The findings warrant the limitations of current health insurance coverage in reducing the financial strain caused by OOPE, despite its potential for reducing economic hardship. The study highlights the need for increased awareness of health insurance, more affordable premiums, and better public healthcare services. Enhancing insurance coverage and improving financial protection mechanisms could play a significant role in advancing UHC and reducing health-related economic burdens on rural communities.